A comparative study between the two Iraqi and German specialist schools of basketball in some physical and skills attributes: A comparative study between the two Iraqi and German specialist schools of basketball in some physical and skills attributes - Sami, Luay (Journal of Physical Education, 2013)
The study aimed to make a comparison between the two Iraqi and German specialist schools of basketball in some physical and skills attributes, and the researcher suppose there are no significant differences between the two basketball schools specialist of Iraqi and German in some physical and skills attributes.Descriptive method used and sample search contain players from specialized basketball school in Iraqi ages (11) and (12) years, the researcher used some physical and skills tests that made for comparison purpose which prepared as a standards for private school in Germany, statistical bag were used (SPSS) to extract research's values, the researcher concluded that German specialist school was superiority on the Iraqi specialized school basketball at the age (11) and (12) years in the skills ability, and explosive power. The researcher recommended that work on application to development Iraqi specialist schools of basketball using modified training programs for increasing skills and physical level for players, and to use their expertise. And work carefully on talented players through the use of standardized tests that made for this purpose, and set up standard for them